2021
DOI: 10.14202/vetworld.2021.678-688
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of putative pathogenic Shewanella algae isolated from ballast water

Abstract: Background and Aim: Shewanella algae is ubiquitous in marine-associated environments and has been increasingly recognized as a significant human pathogen that can cause serious infections mainly associated with exposure to seawater and ingestion of raw seafood. This study aimed to isolate and characterize S. algae from ballast water of ships berthed at Port Klang, Malaysia. Materials and Methods: Ballast water was sampled from nine ships docked at Port Klang, Malaysia. The isolates were identified and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Nevertheless, their antimicrobial resistance pattern indicated that the prevalence of such least reported bacteria also play a key role in spreading AMR among the shrimp pathogens. Higher MAR index of putative pathogen, S. algae was recently reported from marine environments also corroborated with the present study (Ibrahim et al 2021). Even though diverse bacteria were recovered and an overall increased AMR and uniform resistance pattern were observed among the samples from farm 2 compared to farm 1, the MAR index was found to be higher in the case of farm 1 with V. alginoyliticus and V. mimicus as the most resistant ones.…”
Section: Antibiogram Pro Lingsupporting
confidence: 93%
“…Nevertheless, their antimicrobial resistance pattern indicated that the prevalence of such least reported bacteria also play a key role in spreading AMR among the shrimp pathogens. Higher MAR index of putative pathogen, S. algae was recently reported from marine environments also corroborated with the present study (Ibrahim et al 2021). Even though diverse bacteria were recovered and an overall increased AMR and uniform resistance pattern were observed among the samples from farm 2 compared to farm 1, the MAR index was found to be higher in the case of farm 1 with V. alginoyliticus and V. mimicus as the most resistant ones.…”
Section: Antibiogram Pro Lingsupporting
confidence: 93%
“…Furthermore, the ASVs were all annotated as Shewanella algae . Shewanella algae is ubiquitous in the marine environments and has been identified as conditionally pathogenic bacteria that can cause serious infections, primarily associated with exposure to seawater and ingestion of raw seafood, and this group of bacteria can exhibited b-hemolytic activity, strong biofilm-adherence capabilities, and multiple antibiotic resistances [ 37 , 38 , 39 , 40 , 41 , 42 ]. We think that Shewanella algae should not be a dominant group (though it can be present) in melon-headed whales or short-finned pilot whales [ 16 ]; indeed, the overwhelming dominance of Shewanella algae in the gut of PE8 might have been a potential trigger of its death ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the first bla OXA-48 gene in Klebsiella pneumoniae in Istanbul in 2001, there has been a growing number of carbapenem-hydrolyzing class D β-lactamases (CHDLs) found globally [ 7 , 8 , 9 , 10 , 11 ]. Furthermore, an increasing number of OXA-48-like variants capable of carbapenem hydrolysis have been identified in both the clinical and community settings [ 12 , 12 , 13 , 14 , 15 , 16 ]. As carbapenems are considered last-resort antimicrobials in the treatment of Gram-negative bacterial infections, the emergence and spread of OXA variants has garnered significant attention because of the potential risks they present in clinical infection management.…”
Section: Introductionmentioning
confidence: 99%
“…strains are closely associated with human diseases [ 7 , 8 , 9 , 10 ]. The common pathogenic species of Shewanella , including Shewanella xiamenensis , Shewanella algae , and Shewanella putrefaciens [ 11 , 12 ], are derived from various environments such as saltmarsh plants, freshwater, estuarine water, sewage, river water and livestock wastewater [ 12 , 13 , 14 , 15 , 16 , 17 ]. According to the latest clinical reports, skin and soft tissue infections, intestinal colonization, respiratory diseases, bacteremia, intra-abdominal infection, and otitis media are the common complications caused by Shewanella spp.…”
Section: Introductionmentioning
confidence: 99%